الولاية في الزواج: مقاصدها في الشريعة وتحدياتها المعاصرة (Guardianship in the Marriage: Its Objectives in the Shariah and Contemporary Challenges) - بوهدة غالية; بن سيتريس ميسزيري; بن سايح سناء (Journal of Islam in Asia (E-ISSN 2289-8077), 2020)
تأتي هذه الورقة البحثية في معالجة ما ساء من الأفهام وانتشر حول موقف الإسلام من الحريات الفردية في اتخاذ القرارات والمواقف، إذ تتعالى في ذلك بعض الأصوات من دعاة حقوق الإنسان في تصوير الإسلام أنه حجّر على الحريات الفردية وقيدها (الموسى: 2019، مقدمة الكتاب) بصورة تلغي حق الإنسان في اختياراته الخاصة، وفي إطار ذلك الإشكال تدرس هذه الورقة قضية الولاية على المرأة في عقد الزواج، إذ تعمل على إظهار بعض الممارسات التي كرستها الكثير من الأعراف في أن الولاية سلطة مطلقة للولي (الأب، الأخ...) تمنع حق البنت في حرية الاختيار وهذا ما جعل بعض المنظمات الحقوقية النسوية تدعو بالرفع المطلق للولاية في الزواج، وأن الاختيار في الزواج حق محض ومطلق للبنت. وتستند الدراسة إلى منهجين: المنهج الاستقرائي في تتبع وجمع المادة العلمية من المصادر والمراجع ذات العلاقة بالموضوع، والمنهج التحليلي في بيان المفاهيم الصحيحة للولاية وممارساتها في المجتمع، وفي إظهار أوجه الخطورة على حفظ الأسرة المسلمة من دعوات الحقوقين في إلغائها. تهدف هذه الورقة إلى بيان المفهوم الصحيح للولاية في الزواج وأحكامها وشروطها في ضوء مقاصد الشريعة من حيث أنها تعمل على جلب ما فيه نفع للأسرة وضمان استقرارها واستمرارها، ودرء كل ما فيه ضرر متوقع على زواج البنت دون ولاية وليها من حيث بيان مفاسدها في الإخلال بمقاصد الزواج والأسرة باعتبار المآل. وتهدف في نتائجها أيضًا إلى بيان وسائل غرس ثقافة أسرية أصيلة وسليمة لمواجهة التحديات المعاصرة التي تتربص بالأسرة المسلمة في الأمة. الكلمات المفتاحية: الولاية، عقد الزواج، مقاصد الأسرة، التحديات المعاصرة. Abstract This paper deals with the widespread misunderstandings regarding the Islamic standpoint in relation to individual freedom in taking decisions and holding positions as there are arising some voices from human right activists claiming that Islam has abandoned and restricted individual freedoms (Musa: 2019) in such a way where it vialotes the rights of the humans in their private choices. In the same context, this paper tries to study the issue of guardianship in the marriage highlighting some practices which have rooted in many customs giving the impression that guardianship is an absolute authority of the giardians (father, brother…) which deprives the girl to make her own choice. It resulted in some feminists and women rights movements asking for complete abolition of the guardianship in the marriage and demanding full and absolute freedom of marriage for a girl. The present study relies on two methods: inductive method which enables to collect all the academic materials from the related sources, and content analysis method through which correct connotations of guardianship and its practices in the society will be explained highlighting the potential dangers of the demands of complete abolition of the guardianship to the preservation of the family. This paper aims to present the correct understanding on guardianship in the marriage, its rulings and its conditions in the light of Maqasid al-Shariah as it acts to achieve what is beneficial for the family and guarntees its permanence and establishment as well as it removes the potential harms on the marriage of the girl without guardianship. It also indicates its evils as interrupting the objectives of the marriage and family from consequential point of view. As a result, this paper also aims to discusses the resources for inculcating a good and safe family culture which can counter contemporary challenges aiming to destroy the Muslim families of the Ummah. Keywords: Guardianship, Contract of Marriage, Objectives of the Family, Contemporary Challenges.